Monoamine Oxidase Inhibitors as Neuroprotective Agents in Age-Dependent Neurodegenerative Disorders - Naoi, Makoto; Maruyama, Wakako (Current Pharmaceutical Design, 2010)
Alzheimer's and Parkinson's diseases are the most common neurodegenerative disorders among the aged. The etiologies of these diseases remain to be clarified, but the common disease-modifying factors are confirmed: oxidative stress, apoptosis, mitochondrial dysfunction, excitotoxicity, impaired ubiquitine-proteasome system and inflammation. Neuroprotective therapy is proposed to prevent the disease progression by intervening the pathogenic and disease-modifying factors. From the studies on Parkinson's disease, the inhibitors of type B monoamine oxidase, such as selegiline and rasagiline, are the most promising neuroprotective agents to date. These inhibitors protect neuronal cells against cell death induced in cellular and animal models. The neuroprotective functions are ascribed to the stabilization of mitochondria, the prevention of death signaling process and the induction of pro-survival anti-apoptotic Bcl-2 protein family and neurotrophic factors. In cellular models, selegiline and rasagiline increased the different neurotrophic factors classes, neurotrophins (nerve growth factor, brain-derive neurotrophic factor, neurotrophin 3) and ligands of glial cell line-derived neurotrophic factor, respectively. Studies in non-human primates and patients with Parkinson's disease confirmed further the induction of these specified neurotrophic factors. Selegiline and rasagiline are expected to show distinct pharmaceutical activities in selective neuronal systems through induction of distinct neurotrophic factors, and then activation of their own receptors and kinase systems. This review presents the molecular mechanisms behind neuroprotection by monoamine oxidase inhibitors and discusses the possible development of new drugs to prevent, delay and restore the neuronal cell death in Alzheimer's and Parkinson's diseases.
Keywords: MAO inhibitors